2014
DOI: 10.5812/jjm.11014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Characteristics of Kawasaki Disease

Abstract: Background:Kawasaki disease (KD) is an acute multisystem vascular syndrome of unknown etiology that is the leading cause of acquired heart disease in children of developed counties.Objectives:We aimed to evaluate the epidemiological characteristics and clinical manifestations of KD in children residing in the southwest of Iran.Patients and Methods:In this retrospective study, we reviewed the medical records of all children with KD who had been admitted to the main children’s hospital of Ahvaz, southwest Iran, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
(36 reference statements)
7
12
1
4
Order By: Relevance
“…In this regard, Shamsizadeh et al showed that 64 (61.5%) and 40 (38.5%) patients met the diagnostic criteria for typical and atypical KD, respectively. In contrast to our study, fever, along with conjunctivitis and oral changes, was a cardinal sign (11). We found fever in 100% of our patients, followed by polymorphic exanthema.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this regard, Shamsizadeh et al showed that 64 (61.5%) and 40 (38.5%) patients met the diagnostic criteria for typical and atypical KD, respectively. In contrast to our study, fever, along with conjunctivitis and oral changes, was a cardinal sign (11). We found fever in 100% of our patients, followed by polymorphic exanthema.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the majority of patients were born in winter months. This seasonal trend has been also reported in previous studies, in which KD patients were prominently born in February (winter) (11).…”
Section: Discussionsupporting
confidence: 88%
“…The high rate of white blood cells, platelet count, ESR and positive C reactive protein was similar to other reports 17,[19][20][21][22] .…”
Section: Resultssupporting
confidence: 76%
“…In the current study there was seasonal variation, in which we have two cases recorded during autumn and the peak of our cases was reported in winter, spring and early summer, similar to other studies done in Saudi Arabia 16 , Iran 17 and United…”
Section: Resultssupporting
confidence: 65%
“…Menos frecuentes son los surcos transversos en las uñas de las manos y los pies (líneas de Beau). 16,[18][19][20] …”
Section: Fase Subagudaunclassified